(untitled) (Per Musi, 2024)
Music Therapy paradigm sees music as the own therapy, in the creative musical experience. For some models belonging to the paradigm, the process occurs through the relationship between the musicality of three agents: client, music and music therapist, requiring the latter one to be educated in the so-called Clinical Musicianship. This research aims to understand how music-centered music therapists conceptualize, think and search to develop their Clinical Musicianship through the analysis of three semi-structured interviews, carried out with experts in the area, using the Thematic Analysis method (Braun; Clarke 2006). The major theme called Clinical Musicianship was deepened, containing two sub-themes: (1) concepts and characteristics of Clinical Musicianship and (2) development of Clinical Musicianship (self-knowledge, personal therapy and supervision). In conclusion, Clinical Musicianship is important to the music-centered music therapist, in his continuous development, self-knowledge and recognition of limits, and that there is still much more to be studied about this subject.